H‐Mediated Magnetic Interactions between Layers in a 2D MnII–Dicyanamide Polymer: Neutron Diffraction, DFT, and Quantum Monte Carlo Calculations. Issue 3 (15th January 2018) - Gillon, Béatrice; Hammerschmied, Albert; Gukasov, Arsen; Cousson, Alain; Cauchy, Thomas; Ruiz, Eliseo; Schlueter, John A.; Manson, Jamie L.
Abstract: Invited for the cover of this issue are Beatrice Gillon from LLB (CEA‐CNRS), France, Jamie L. Manson from Eastern Washington University, USA, and co‐workers. The cover image shows the experimental magnetic phase diagram of a quasi bidimensional Mn II –dca polymer and the magnetic structures of the ordered phases. The spin density, as determined in the paramagnetic phase, validates an important magnetic pathway mediated by interlayer hydrogen bonds. Abstract : We envisage that these materials will have potential applications in quantum information storage and processing… Read more about the story behind the cover in the Cover Profile and about the research itself in theFull Paper by B. Gillon, J. L. Manson et al.